Complementary and alternative medicine in pediatrics in Turkey - Özturk, Candan; Karataş, Hülya; Laengler, Alfred; Schuetze, Tim; Bailey, Rebekka; Zuzak, Tycho Jan (ZHEJIANG UNIV SCH MEDICINE, 2014)
Background: Complementary and alternative medicine (CAM) is applied both to children and adults widely throughout the world. A previous pan-European survey showed a surprisingly high CAM-use in Turkish children. This review aimed to survey information on the use of CAM in pediatrics in Turkey. Data sources: A narrative, non-systematic review was conducted by melding expert opinions with a thorough and balanced review of available evidence. An unrestricted literature search using the key words, "alternative", "complementary", "integrative", "prevalence" and "pediatric" or "children" and "Turkey" was performed by internet search in March, 2012 using PubMed and Google Scholar. Results: CAM use was examined in general pediatrics, pediatric oncology, patients with asthma, and patients with diabetes. A frequency of CAM use was 87% in Turkish pediatric patients, with a mean of 60%. The primary sources of information about CAM are family and friends. Communication with patients/parents and health care professionals showed that most parents do not speak about CAM use with their physicians or nurses. Conclusions: CAM is extensively used in Turkish pediatric patients. This might be due to Turkey's status as a developing country in which a traditional medical system still dominates in comparison to developed countries. Thus, larger studies are required to prove an extensive use of CAM in Turkey, as this review article does not have the capacity for in-depth analysis. Knowledge about CAM and its related topics is essential for physicians and nurses in order to meet the patients' wish for a competent consultation concerning all aspects of a possible therapy.
WOS: 000344841300002
PubMed ID: 25515802
Keywords: Acupuncture; Alternative medicine; Herbal medicine; Homeopathy; Mind-body